Comparing the effect of standardized patient-based education and feedback lecture on midwives' knowledge and practice in counseling screening for fetal malformations - Maryam Javidi-Sarafan; Mahin Tafazoli; Talat Khadivzadeh; Seyed Reza Mazloum (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Midwifery screening is one of the duties of midwives according to national guidelines. It is possible to increase midwives' knowledge and practice through effective education. The aim of this study was to compare the effect of standardized patient-based education and feedback lecture on midwives' knowledge and practice in screening counseling for fetal malformations. METHODS: This quasi-experimental, two-group study (standardized patient-based training and feedback lecture) was performed on 67 midwives (licensed by the office) in Mashhad in 2018. Midwives' knowledge and practice before and 2 weeks after training (a 4-h training program) were assessed by the Objective Structured Clinical Examination and a questionnaire. The data were analyzed by the SPSS software version 16 using Mann-Whitney, Chi-square, Wilcoxon and independent t-test while P < 0.05 considered as a significant level. RESULTS: Before intervention, the total score of knowledge and practice showed no statistically significant difference between the two groups (P > 0.05). After intervention, knowledge score in feedback lecture group was statistically significantly higher than that of standard patient group (P < 0.001). In addition, there was no statistically significant difference in performance scores between the two groups after intervention (P = 0.761). CONCLUSION: Both educational methods can increase midwives' knowledge and practice in fetal screening counseling. However, in raising midwives' awareness, feedback lecture group was more effective than standard patient group.